Redescription of Odontoscirus iota Atyeo (Acari: Trombidiformes: Bdellidae) from Iran, with a key to the Iranian species of Odontoscirus - Saeid Paktinat-Saeij; Aylar Rostami; Mohammad Bagheri; Saeid Valizadeh (Persian Journal of Acarology)
Odontoscirus iota Atyeo, 1960 is reported here for the first time from Iran. An additional description is provided for O. iota based on adult females collected from East Azerbaijan province, northwest of Iran. An updated key to the species of Odontoscirus from Iran is presented.